Mucosal-Associated Invariant T Cell Levels Are Reduced in the Peripheral Blood and Lungs of Children With Active Pulmonary Tuberculosis - Malka-Ruimy, Clara; Ben Youssef, Ghada; Lambert, Marion; Tourret, Marie; Ghazarian, Liana; Faye, Albert; Caillat-Zucman, Sophie; Houdouin, Véronique (Frontiers in Immunology, 2019)
Abstract Mucosal associated invariant T (MAIT) cells are unconventional, semi-invariant T lymphocytes that recognize microbial-derived vitamin B2 (riboflavin) biosynthesis precursor derivatives presented by the monomorphic MHC class 1-related (MR1) molecule. Upon microbial infection, MAIT cells rapidly produce cytokines and cytotoxic effectors, and are thus important players in anti-microbial defense. MAIT cells are protective in experimental models of infection and are decreased in the blood of adult patients with bacterial infections, including Mycobacterium tuberculosis (Mtb). In children, the risk of rapid progression to active tuberculosis (TB) following Mtb infection is higher than in adults. Whether MAIT cells influence the outcome of Mtb infection in children is therefore, an important issue. We analyzed MAIT cell numbers and phenotype in 115 children investigated for pulmonary TB and determined their potential correlation with disease progression. MAIT cells were reduced in numbers and activated in the peripheral blood of children with active TB as compared to those with latent TB infection and healthy children. Moreover, MAIT cells did not accumulate and did not proliferate in the lung of children with active TB. These results suggest that MAIT cells may be important in preventing progression of Mtb infection to active TB in children.